Church and agapocracy: The rule of love - Van de Beek, Abraham (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
At the heart of Christian faith and the life of the Church lies the conviction that God is love and that this is the rule by which the Christian community and indeed all of humanity is to be guided and judged. However, responding to the Scriptural witness of love as agapè – as practical faithfulness and self-giving to “the other” – is challenging and quite often very problematic. What is involved in “loving the Lord your God”? What is asked of us in the command to “love one’s enemy as oneself”? How is the Church called to manifest agapè in society? This contemplative essay reflects on these questions, revealing what is at stake in current debates in ecclesiology, ethics and the Christian life where love is claimed to rule.